(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
The present study was designed to assess the modulatory effects of Aloe vera on chromium-induced alterations in renal and testicular tissues of mice. For this study, male Balb/c were divided into four groups: Group I (control), Group II (PD) [orally administered with potassium dichromate], group III (AV) [orally administered with Aloe vera] and group IV (AV+PD) [administered with Aloe vera and potassium dichromate]. Histopathological alterations and levels of renal (urea, blood urea nitrogen, uric acid, creatinine) and testicular (sperm count and motility) organ function markers indicated damage to these organs. This was accompanied by increased serum lactate dehydrogenase activity. Chromium appeared to weaken the DNA repair machinery of the cells, as observed from the decrease in mRNA expression of DNA-PK and MGMT genes in renal tissue. Improvement in histoarchitecture and functional markers of organs, decrease in cell damage marker, and increased expression of DNA repair-associated genes are indicative of protection rendered by A. vera against chromium-induced harmful effects. This preliminary study indicates the beneficial effects of A. vera against heavy metal toxicity. However, it is imperative to exhaustively study the possible modulatory effects of A. vera and decipher the underlying mechanisms at play during the amelioration of chromium-induced toxicity. Such studies would warrant its use against managing heavy metal toxicity.